Distribution, richness, and molecular identification of spider crabs (Brachyura: Majoidea: Mithracidae) from Costa Rica - Sancho-Blanco, Carolina (2022)
The objective of this study was to determine the distribution, richness, and molecular identification of spider crabs in the Costa Rican Pacific and Caribbean coasts. Distribution maps were created for species of the Mithracidae family on the Caribbean and Pacific coasts of Costa Rica, based on exploratory samplings and spatio-temporal records of collections (1960 to 2016) provided by the Universidad de Costa Rica’s Museum of Zoology. In addition, phylogenetic relationships were explored using a multigene concatenated phylogenetic tree based on mitochondrial and nuclear gene fragments. Historical records reveal the presence of 24 species of mithracid crabs and their geographic distribution in the Pacific and Caribbean of Costa Rica, including islands on the continental and oceanic shelf. Molecular analyses confirm sister relationships between the clades Ala-Maguimithrax, Omalacantha-Microphrys, Omalacantha+Microphrys-Teleophrys, and a well-supported clade of species belonging to the genus Mithraculus. However, our concatenated molecular data set suggests a monophyletic relationship between Thoe, Petramithrax, and Hemus, differing from what was previously reported. The results obtained in this study will help in the development of strategies for the environmental protection of these marine resources, by providing a baseline for monitoring environmental degradation and destruction of habitats used by spider crabs on the coasts of Costa Rica. Furthermore, the molecular information obtained in this study will help future studies focusing on understanding the population genetics, phylogeography, regional gene flow, and divergence among species between the Caribbean and Pacific coast.